The Role of Preprocedure Genetic Counseling in Pregnancies Interrupted for Fetal Abnormalities - Francoeur, Alex A.; Kang, Sung-Hae L.; Senaratne, T. Niroshi; Saitta, Sulagna; Murali, Aparna; Peters, Katharine; Hansman, Emily; Chen, Angela; Parvataneni, Ram; Patil, Rajita; Rible, Radhika; Sridhar, Aparna; Stoddard, Amy; Zapata, Mya; Krakow, Deborah; Pluym, Ilina D. (American Journal of Perinatology, 2023)
Objective Congenital birth defects affect 3 to 5% of pregnancies. Genetic counseling can help patients navigate the testing process and understand results. The study objective was to identify predictors and utility of genetic counseling at the time of pregnancy termination. Additionally, we aimed to see what proportion of patients would benefit from additional testing based on the results of the genetic testing.Study Design This was a retrospective cohort review of all terminations performed for fetal anomalies by an academic center from July 2016 to May 2020. Indications were stratified by abnormal serum screening or types of abnormal ultrasound findings. Data were abstracted regarding uptake of genetic counseling and testing results. Abnormal results that warranted additional testing regarding recurrence risks were noted. Multivariable logistic regression was performed to identify predictors of receipt of genetic counseling and testing.Results Of 387 patients, 57% (n = 220) received preprocedure genetic counseling and 43% (n = 167) did not. Among patients who received diagnostic testing, 62% (n = 194) had genetic counseling compared with 38% (n = 121) without counseling (adjusted odds ratio 2.46, 95% confidence interval [1.41–4.29], p < 0.001). Among the entire cohort, 38% (n = 148) had suspected aneuploidy based on serum screening. Of these, 89% (n = 132/148) had definitive testing, 92% (n = 122/132) confirming the aneuploidy. Among the other 68% (n = 239) with structural anomalies, 76% (n = 183) had diagnostic testing with 29% (n = 53) yielding an abnormal result. Among those fetuses with structural anomalies, 36% (n = 19/53) of genetic diagnoses warranted additional parental testing because of risk of recurrence compared with only 2% (n = 2/122) of patients with abnormal serum screening results alone.Conclusion Genetic counseling was associated with increased uptake of diagnostic testing, which yielded useful information and prompted additional testing. This is important for determining etiology and recurrence risk and should be offered to patients presenting for termination for fetal indications, as well as providing diagnostic closure for patients.Key Points
Keywords: karyotype; microarray; pregnancy termination; genetic counseling; future pregnancies; recurrence risk